Implementação de processo para fabricação de peças aplicado à indústria de papel e celulose - OLIVEIRA, Jaqueline Silva de (2022)
The manufacture of spare parts for industrial maintenance is relevant for companies as it ensures that their physical structure, machinery and equipment will be available to meet production demand. By investing in the manufacture of industrial parts, it is possible to guarantee a complete infrastructure prepared to meet the needs of customers, which is essential for any business to stand out in the market. In this context, the manufacture of bespoke industrial parts is highly recommended because it ensures that the company will have at its disposal the most appropriate solutions for the type of activity performed. However, in order to enjoy all the benefits that the manufacture of industrial parts is capable of providing, it is essential that there is a structured process for the manufacture of spare parts that guarantees quality in the manufacturing processes. In this way, it is proposed the implementation of a spare parts manufacturing process using machines by computer number command, machine programming software and reverse engineering, in addition to dimensional control equipment in a pulp and paper industry located in the Southeast. of the state of Maranhao. The process allowed parts to be manufactured on demand that were delivered with a dimensional report and analysis of the chemical composition of the materials used in their production, thus ensuring their reliability. This process corroborated with the reduction of costs with the acquisition of parts for the industrial maintenance area of the company under study. The results achieved confirmed the viability of the process and demonstrate that investing in the manufacture of custom-made industrial spare parts is a strategic attitude with the potential for great benefits and financial return.